PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN HUTANG DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Damarani, Filosofia; Kusbandiyah, Ani; Amir, Amir; Mudjiyanti, Rina (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of this research is to test the effect of managerial ownership, institutional ownership, debt policy, and firm size on firm value in the basic materials sector in the 2019-2022 period. This research analyzes secondary data which is called quantitative research. The sampling technique in this research was purposive sampling and a sample of 24 companies was produced that met the criteria. The results of this research show that: (1) managerial ownership has no influence on firm value, (2) institutional ownership has a positive influence on firm value, (3) debt policy has a positive influence on firm value, (4) firm size has a negative influence on firm value. This suggests that the control exercised by managers over company shares may not be a determining factor in determining overall company value. Then, the findings also show that the company benefits from institutional investors, which implies that the trust and support of these investors contributes positively to the company's perceived value. Additionally, this research underscores the beneficial impact of a well-managed debt strategy on increasing overall firm value. In contrast, this research reveals a negative relationship between company size and company value, indicating that large companies may face challenges or problems that have a negative impact on overall company value.